PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS MULTIPLE INTELLIGENCES PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN - Septiani, Dwi; Ridlo, Saiful; Setiati, Ning (Journal of Biology Education, 2013)
This study aimed to develop and assess feasibility of student worksheet on Growth and Development topics, based on multiple intelligences theory, as well as to measure the effectiveness ofÂ  the student worksheet. Research design usedÂ  was one of research and development modified from Sugiyono (2010), and was based on studentsâ intelligences identification and teaching materials analyzed. LKS validation results were analyzed with descriptive percentages. Small-scale testing wasÂ  carried out on 1 teacher and 12 students to assess worksheets legibility. Large-scale field-testing was carried out on one teacher and 36 students to measure student worksheetsâ effectiveness. Results of student worksheet development based on multiple intelligences theory in terms ofÂ  its material feasibility aspects wasÂ  96,87% (obtained score) and media feasibility 89,56% under medium category. Normalized gain score was 0,65, indicating thatÂ  there was an increasing learning achievementÂ  from pretest to posttest under medium category. Classical completeness ofÂ  students reached 88,89%. The use ofÂ  the student worksheet forÂ  learning process was appreciated â very good responsesâ byÂ  teachers and students, 100% and 88,69%. Student worksheet developmentÂ  on the basis of multiple intelligence theories forÂ  Growth and Development topics wasÂ  feasible and effectively applied forÂ  learning.Â Penelitian bertujuan untuk mengembangkan dan mengetahui kelayakan Lembar Kerja Siswa (LKS) berbasis multiple intelligences pada materi pertumbuhan dan perkembangan serta mengukur keefektifan LKS dalam pembelajaran. Penelitian menggunakan metode penelitian pengembangan (Research and Development) dimodifikasi dari Sugiyono (2010) berdasarkan hasil identifikasi kecerdasan siswa dan analisis kebutuhan bahan ajar. Hasil validasi LKS dianalisis dengan deskriptif persentase. Uji coba skala kecil dilakukan terhadap 1 guru dan 12 siswa untuk menilai keterbacaan LKS. Uji coba skala besar dilakukan terhadap 1 guru dan 36 siswa untuk mengukur efektivitas LKS dalam pembelajaran. Hasil pengembangan LKS berbasis multiple intelligences aspek kelayakan materi memperoleh skor 96,87% dan kelayakan media 89,56% dengan kategori sangat layak. Nilai gain ternormalisasi sebesar 0,65 menunjukkan adanya peningkatan hasil belajar dari pretest ke posttest dengan kategori sedang. Ketuntasan klasikal siswa mencapai 88,89%. Penggunaan lembar kerja siswa dalam pembelajaran memperoleh tanggapan sangat baik dari guru dan siswa dengan persentase 100% dan 88,69%. Pengembangan lembar kerja siswa berbasis multiple intelligences pada materi pertumbuhan dan perkembangan layak dan efektif diterapkan dalam pembelajaran.